Study of Different Rates of Application of Pendimethalin and Acetochlor on Weed Infestation and Grain Yield of Fababean - Hajjaj B.; Tantaoui H.; El Oualkadi A. (European Scientific Journal, ESJ, 2019)
A fababean weed control trial was conducted during the 2016-2017 growing season. The aim of this study is to investigate the effect of two preemergence herbicides Pendimethalin and Acetochlor on weed infestation in a fababean crop. Dominant weed botanical families in the experimental site belong to Asteraceae and Poaceae. Results showed that the improvement of fababean grain yield depends on the weed control efficacy. Treatment with Pendimethalin at 1228 g/ha widely decrease fababean weed infestations recording 91.7% and 90.56 respectively on visual efficacy rating and weed biomass reduction. Acetochlor at 1050 g/ha recorded the lowest efficacies 53.3% and 62.1% respectively on visual efficacy rating and weed biomass reduction. Plots treated with Pendimethalin at 1228 g/ha recorded the best yields with an average of 3.32 tons / ha.